2011
DOI: 10.1097/nmd.0b013e31820caefb
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy Versus Second-Generation Antidepressants in the Treatment of Depression

Abstract: Most meta-analyses have concluded that psychotherapy and pharmacotherapy yield roughly similar efficacy in the short-term treatment of depression, with psychotherapy showing some advantage at long-term follow-up. However, a recent meta-analysis found that selective serotonin reuptake inhibitors medications were superior to psychotherapy in the short-term treatment of depression. To incorporate results of several recent trials into the meta-analytic literature, we conducted a meta-analysis of trials which direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 41 publications
4
59
1
3
Order By: Relevance
“…Les revues systématiques d'ECR ont été prises en compte et certaines limites méthodologiques ont été relevées dans ces ECR. Celles-ci ont trait, entre autres, à l'utilisation préalable ou concomitante de médicaments ou de la psychothérapie chez les participants, au transfert de patients dans l'autre groupe de traitement en l'absence de réponse au traitement initial, à l'augmentation de la dose ou au changement du type d'antidépresseur en cours de traitement, alors que ce type d'ajustement n'est pas possible dans le cas de la psychothérapie, et à l'exclusion des patients qui ne répondent pas à une thérapie lors du prétest (Spielmans, et al, 2011).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Les revues systématiques d'ECR ont été prises en compte et certaines limites méthodologiques ont été relevées dans ces ECR. Celles-ci ont trait, entre autres, à l'utilisation préalable ou concomitante de médicaments ou de la psychothérapie chez les participants, au transfert de patients dans l'autre groupe de traitement en l'absence de réponse au traitement initial, à l'augmentation de la dose ou au changement du type d'antidépresseur en cours de traitement, alors que ce type d'ajustement n'est pas possible dans le cas de la psychothérapie, et à l'exclusion des patients qui ne répondent pas à une thérapie lors du prétest (Spielmans, et al, 2011).…”
Section: Discussionunclassified
“…Les paramètres de résultats examinés ne sont pas présentés de façon détaillée et n'ont pas fait l'objet d'une méta-analyse. Les résultats de la mise à jour réalisée afin de compléter la revue australienne de référence incluaient 12 revues systématiques, y compris les méta-analyses, dont : -2 revues systématiques qui traitent à la fois des troubles dépressifs et des troubles anxieux (Cuijpers et al, 2013 ;Roshanaei-Moghaddam et al, 2011) (Bell & D'Zurilla, 2009 ;Cuijpers, Andersson, Donker, & Van Straten, 2011 ;Cuijpers, Reynolds, et al, 2012 ;Cuijpers, Van Straten, Warmerdam, & Andersson, 2009 ;Gould, Coulson, & Howard, 2012 ;Khan, Faucett, Lichtenberg, Kirsch, & Brown, 2012 ;Spielmans, Berman, & Usitalo, 2011 ;Van Hees, Rotter, Ellermann, & Evers, 2013) incluant environ 138 études avec 18 707 patients ; -et 1 revue systématique qui porte uniquement sur les troubles anxieux (Canton, Scott, & Glue, 2012) incluant 9 ECR totalisant environ 922 patients.…”
Section: Caractéristiques Des éTudes Inclusesunclassified
“…19 Psychiatrists who provide comprehensive psychiatric care can readily accommodate patient preferences, which is associated with better treatment retention and outcomes. 19 Recent meta-analyses suggest that treatment with psychotherapies or pharmacotherapy for depression or anxiety disorders achieve comparable outcomes, 1,4,19 and that for patients with severe and chronic illness courses, combination treatment may be advantageous. 20,21 Adjunctive use of psychotherapy has also been shown to improve outcomes in more severe psychiatric disorders, such as bipolar disorder 22 and schizophrenia, 23 which have historically been treated with pharmacotherapy and case management.…”
Section: Discussionmentioning
confidence: 99%
“…D espite a growing evidence base for psychotherapy in the treatment of psychiatric disorders, [1][2][3][4][5][6] American survey data suggest that the provision of psychotherapy by psychiatrists has been diminishing and that now only a small minority of psychiatrists provides psychotherapy to most of their patients. [7][8][9] According to an analysis of over 14 000 patient visits to office-based psychiatrists in the United States, the proportion of appointments involving psychotherapy declined from 44.4% in 1995-1996 to 28.9% in 2004-2005, extending a trend observed since the mid-1980s.…”
Section: Limitationsmentioning
confidence: 99%
“…These psychosocial treatments have demonstrated absolute efficacy not only in the treatment of depression, anxiety, psychosis, and personality disorders, but also in areas such as chronic pain and medication compliance (Beck and Dozois, 2011;Gray et al, 2002;Hayes, Masuda et al, 2004;Linehan et al, 2006). In addition, many of these psychological interventions have demonstrated strong comparative efficacy with medications in the acute treatment of a number of psychological disorders, and with a significantly lower relapse rate in follow-up (Spielmans et al, 2011). Numerous studies using functional neuroimaging have demonstrated that both psychotherapy and psychopharmacology effect changes in brain activity, with these changes overlapping partially-but not completely-with one another (Roffman et al, 2005;Dichter et al, 2010).…”
Section: Introductionmentioning
confidence: 99%